COSMIC MANEUVERS: INNOVATING SATELLITE FLEXIBILITY WITH ADVANCED ATTITUDE AND VIBRATION TECHNIQUES - Li , Wei Zhang; Jun , Feng Wang (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Early space exploration was characterized by relatively small lunar equipment, which necessitated straightforward mechanical models and limited changes in elastic models. Satellites designed during this period, whether actively controlled or passively stabilized, were often treated as rigid bodies in motion. However, the landscape of space missions has evolved over time, leading to the widespread use of larger spacecraft. The diverse array of missions demands higher standards for spacecraft state, action precision, stability, and endurance [1]. Consequently, addressing the issue of coupling between the flexible satellite's attitude control system and the flexible structure has become pivotal. Unlike rigid body dynamics, which are commonly employed in planet manipulation, flexible components are more complex, and their motion is not simplistically treated as rigid body movement. Violent oscillations of these flexible components can pose a threat to the integrity of the control system. In light of the increasing use of flexible spacecraft for Earth observation and the growing importance of precise pointing in flexible launch vehicle operations, it has become imperative to conduct an indepth study of flexible launch vehicle attitude control modes.